Association of nocturnal sleep duration and midday napping with subjective poor hearing among middle-aged and older adults in China - Cui, Xiaorui; Lu, Zixuan; Guo, Xinyue; Dai, Neng; Huang, Chen; Liu, Yahang; Lin, Ruilang; Yu, Yongfu; Qin, Guoyou; Chen, Jiaohua (Frontiers in Public Health, 2023)
Background: Hearing loss has occurred as a critical concern for aging and health. However, it remains unknown whether nocturnal sleep and midday napping duration are associated with hearing loss in middle-aged and older adults. Methods: The study comprised 9,573 adults from China Health and Retirement Longitudinal Study, who have completed the survey for sleep characteristics and subjective functional hearing. We collected self-reported nocturnal sleep duration (<5, 5-<6, 6-<7, 7-<9, ≥9 hours/night) and midday napping duration (≤5, 5-≤30, and >30 minutes). The sleep information was classified into different sleep patterns. The primary outcome was self-reported hearing loss events. Multivariate Cox regression models and restricted cubic splines were used to investigate the longitudinal association of sleep characteristics with hearing loss. We applied Cox generalized additive models and bivariate exposure-response surface diagrams to visualize the effects of different sleep patterns on hearing loss. Results: We confirmed 1,073 cases of hearing loss (55.1% female) during the follow-up. After adjusting for demographic characteristics, lifestyle factors and health condition, nocturnal sleep with <5h was positively associated with hearing loss[hazard ratio (HR): 1.45, 95% confidence interval [CI]: 1.20, 1.75]. Individuals with napping for 5-≤30 minutes had a 20% (HR: 0.80, 95%CI: 0.63, 1.00) lower risk of hearing loss compared with those with napping ≤5 minutes. Restrictive cubic splines showed the reverse J-shaped association between nocturnal sleep and hearing loss. Moreover, we found significant joint effects of sleeping <7 hours/night and midday napping ≤5 minutes (HR: 1.27, 95% CI: 1.06, 1.52) on hearing loss. Bivariate exposure-response surface diagrams also reflected the finding that short sleep without napping existed the highest risk of hearing loss. Compared with persistently sleeping moderately (7-9 hours/night), those who persistently slept <7 hours/night or shifted from <7 hours/night to moderate or >9 hours/night had higher risks of hearing loss. Conclusion: Inadequate nocturnal sleep was associated with an elevated risk of poor subjective hearing in middle-aged and older adults, while moderate napping decreased the risk of hearing loss. Keeping sleep stable within recommendation duration may be a useful strategy for preventing poor hearing loss.